Elevated antinuclear antibodies and unprovoked venous thromboembolism: a case-control study - Delkash, Parisa; Kharazmi, Amir Behnam; Tamartash, Zahra (Novelty in Biomedicine, 2025)
Background: Unprovoked venous thromboembolism (VTE) can occur without traditional risk factors, and its underlying causes remain poorly understood. This study investigates the potential role of elevated antinuclear antibody (ANA) titers as a biomarker for unprovoked VTE. Materials and Methods: A case-control study was conducted with 189 patients diagnosed with unprovoked VTE, and 189 matched controls without VTE between 2019 and 2023. ANA titers were measured using enzyme-linked immunosorbent assay (ELISA), and the association between elevated ANA titers and unprovoked VTE was assessed. Results: The study revealed a significant association between elevated ANA titers and unprovoked VTE. The case group had a higher proportion of patients with ANA titers >1:100 (14.3%) compared to controls (3.7%) (p<0.001). Laboratory analysis showed significantly higher white blood cell count (p<0.001), lower mean corpuscular volume (p=0.03), and higher creatinine levels (p<0.001) in the case group. No significant differences were observed in hemoglobin or platelet levels (p=0.07 and p=0.89, respectively). Conclusion: Elevated ANA titers may serve as a useful biomarker for identifying patients at risk for unprovoked VTE. Clinicians should consider autoimmune disorders in the differential diagnosis for unprovoked VTE. Early detection of elevated ANA could lead to targeted interventions and improved patient outcomes by reducing VTE recurrence and managing underlying autoimmune conditions.